1996
DOI: 10.1103/physrevlett.77.1950
|View full text |Cite
|
Sign up to set email alerts
|

Improved Upper Limit on Muonium to Antimuonium Conversion

Abstract: A new experiment has been set up at the Paul Scherrer Institut to search for muonium to antimuonium conversion. No event was found to fulfil the requested signature which consists of the coincident detection of both constituents of the antiatom in its decay. Assuming an effective ͑V 2 A͒ 3 ͑V 2 A͒ type interaction an improved upper limit is established for the conversion probability of P MM # 8 3 10 29 (90% C.L.), which is almost 2 orders of magnitude lower compared to previous results and provides a sensitive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In fact, in [32] it was found that R g < 0.0030. The results of other experiments in which R g has been measured at different energies can be found in [33] (R g ≤ 0.14) and in [34] (R g ≤ 0.008). The evaluation which follows from Eq.…”
Section: Muonium-positronium Conversionmentioning
confidence: 71%
“…In fact, in [32] it was found that R g < 0.0030. The results of other experiments in which R g has been measured at different energies can be found in [33] (R g ≤ 0.14) and in [34] (R g ≤ 0.008). The evaluation which follows from Eq.…”
Section: Muonium-positronium Conversionmentioning
confidence: 71%
“…6 A weaker upper limit on the same combination of parameters can be derived from searches of muonium anti-muonium transition [36,37]. In general, present limits on the flavor diagonal coupling h ee from Bhabha scattering [38], and other combinations of h ij from rare τ decays are much weaker (typically B τ →lal b lc < 10 −6 [30]).…”
Section: E Testing the Model: Interplay With Collider Measurementsmentioning
confidence: 99%
“…For the doubly-charged bilepton Y −− a tighter lower bound has been found recently from muonium -antimuonium conversion limits, also at PSI [18]. The data require that…”
Section: Bileptonsmentioning
confidence: 99%
“…[22,12] shown in Table I Two lower bounds on m(Y ++ ) exist in the literature: 360 GeV from Ref. [18], and very recently 850 GeV from Ref. [23].…”
Section: Bileptonsmentioning
confidence: 99%